92.0k views
2 votes
(10x²)(-6x² + 3x -8)
Find the product

2 Answers

5 votes

(10x²)(-6x² + 3x - 8) =

= - 60⁴ + 30x³ - 80x²

User Deepkimo
by
5.3k points
0 votes

Answer: -60x^4 + 30x^3 - 80x^2

===================================

Step-by-step explanation:

The distribution rule says to multiply the outer term by each term inside the parenthesis.

We'll multiply the outer term 10x^2 with each term inside -6x^2, 3x and -8

---------

10x^2*(-6x^2 + 3x - 8)

10x^2*(-6x^2) + 10x^2*(3x) + 10x^2*(-8)

-60x^4 + 30x^3 - 80x^2

User Ruvim
by
5.4k points